Replication Data for "Perceptions of Relative Deprivation and Women's Empowerment" - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
These files comprise dataset and do-files for reproducing results presented in the article, "Perceptions of Relative Deprivation and Women's Empowerment" (Kosec, Mo, Schmidt, and Song, 2021). The dataset "Data_PNG_all_tables" is constructed from the Papua New Guinea Household Survey on Food Systems, 2018. A detailed description of each variable in this dataset is included in section 4 of the article. The sampling procedure employed and the raw data are described in the publication "Papua New Guinea Survey Report: Rural Household Survey on Food Systems" (Schmidt et al., 2019).